Peningkatan Hasil Belajar PKn tentang Rumusan Pancasila dengan Jembatan Pintar pada Siswa Kelas VI SD Negeri Nguwet - Sunarso, Sunarso (Paedagogie, 2019)
This research aims to determine the increase of student’s activity and achievement in SD Negeri Nguwet by using Jembatan Pintar in learning Civics. The subjects are teacher and all sixth grade students who consists of 17 boys and 20 girls. It is divided into of two cycles. Data were collected through tests and analyzed using descriptive analysis techniques. It compares the results between the initial data, cycle I, Cycle II and responses found during the classroom activities. Results of the research indicates an increase. The student’s activity improves to be enough in cycle I and be very good in cycle II. Overall the implementation of Jembatan Pintar can enhance students’ engagement and achievement. It can be used not only learning Civics but also all of subjects in school.